2020
DOI: 10.1136/bmjnph-2020-000080
|View full text |Cite
|
Sign up to set email alerts
|

How does self-perceived nutrition competence change over time during medical training? A prospective longitudinal observational study of New Zealand medical students

Abstract: ObjectivesMedical nutrition education aims to equip doctors with nutrition knowledge, skills, attitudes and confidence to counsel patients to improve their diet. This study aimed to describe changes in medical students’ self-perceived nutrition competence at three time points during medical training.DesignProspective longitudinal observational study.SettingThe University of Auckland, School of Medicine.ParticipantsYear 2 medical students (phase 1, preclinical) were surveyed in May 2016. Participants repeated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…The positive association between nutrition education and greater confidence in nutrition knowledge, skills, attitudes and counselling and communication techniques was broadly in line with previous studies. 29 , 30 A low confidence in keeping up to date with peer-reviewed evidence in nutrition and chronic disease and the ability to formulate a meal plan for individuals was reported in our study. Similarly, low confidence in these questions have been reported in other studies on a mixed samples of qualified healthcare professionals 29 , 31 and personal trainers.…”
Section: Discussionmentioning
confidence: 57%
“…The positive association between nutrition education and greater confidence in nutrition knowledge, skills, attitudes and counselling and communication techniques was broadly in line with previous studies. 29 , 30 A low confidence in keeping up to date with peer-reviewed evidence in nutrition and chronic disease and the ability to formulate a meal plan for individuals was reported in our study. Similarly, low confidence in these questions have been reported in other studies on a mixed samples of qualified healthcare professionals 29 , 31 and personal trainers.…”
Section: Discussionmentioning
confidence: 57%
“…However, given the small sample sizes, this cannot be stated for certain. In contrast to Crowley et al (2020), whose authors reported that across-the-board, students gave themselves low ratings of confidence in nutrition skills, participants in this project had an average pre-intervention score of 3.36, closer to <somewhat confident= and postintervention average score of 3.75 closer to the <very confident= ranking. However, in concordance with the Crowley et al ( 2020) study, all participants, regardless of the intervention, agreed/strongly agreed that they needed further nutrition education to help support them in their healthcare role.…”
Section: Outcomes and The Literaturecontrasting
confidence: 81%
“…Residents' barriers to learning and providing nutrition counseling included: lack of time, lack of reimbursement, perceived lack of interest in nutrition, and lack of interest of preceptors in teaching nutrition. Along similar lines, Crowley et al (2020) found that limited exposure to nutrition experts, a lack of interprofessional nutrition collaboration, and a lack of role modeling of nutrition care were all major barriers to students9 learning. Furthermore, even if students received nutrition education in the didactic portion of their learning, it was rare that they experienced any clinical nutrition learning (Crowley et al, 2020).…”
Section: Inconsistent Education Of Healthcare Students and Education ...mentioning
confidence: 89%
See 2 more Smart Citations